2005
DOI: 10.15381/rpb.v12i1.2369
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación larvicida de suspensiones acuosas de Annona muricata Linnaeus «guanábana» sobre Aedes aegypti Linnaeus (Diptera, Culicidae)

Abstract: EL presente trabajo evaluó la toxicidad larvicida de suspensiones acuosas provenientes de extractos etanólicos de las semillas, flores, hojas, corteza de ramas y corteza de raíces de Annona muricata L. «guanábana» sobre larvas del IV estadio de Aedes aegypti para determinar de esta manera los niveles de susceptibilidad. El mayor efecto tóxico correspondió a la suspensión de las semillas con un 100% de mortalidad a las 24 horas a 0,5 mg/mL, seguidos por las flores a las 48 horas a 10 mg/mL y hojas a las 36 hora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
13
0
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 6 publications
5
13
0
9
Order By: Relevance
“…Further, if the extract was initially defatted with hexane, the LC50 was found to be 74.68 μg/mL, and the instar stage of the mosquito larvae was irrelevant (Morales et al, 2004). Therefore, our results are more similar to the results of Bobadilla (2005) and Morales (2004). However, the activity of the A. muricata ethanol extracts against Artemia salina resulted in an LC50 of 0.49 μg/mL for the leaves and 210 μg/mL for the seeds (Luna et al, 2006;Rojas et al, 2004).…”
Section: Aedes Aegypti Larvae Lethality Bioassays and Chromatographicsupporting
confidence: 92%
See 1 more Smart Citation
“…Further, if the extract was initially defatted with hexane, the LC50 was found to be 74.68 μg/mL, and the instar stage of the mosquito larvae was irrelevant (Morales et al, 2004). Therefore, our results are more similar to the results of Bobadilla (2005) and Morales (2004). However, the activity of the A. muricata ethanol extracts against Artemia salina resulted in an LC50 of 0.49 μg/mL for the leaves and 210 μg/mL for the seeds (Luna et al, 2006;Rojas et al, 2004).…”
Section: Aedes Aegypti Larvae Lethality Bioassays and Chromatographicsupporting
confidence: 92%
“…Two previous reports measured an LC50 of 60 (50-70) and 900 (380-1300) μg/mL, respectively, for A. muricata extracts toward the 4 th instar A. aegypti larvae (Bobadilla et al, 2005;Henao et al, 2007). Further, if the extract was initially defatted with hexane, the LC50 was found to be 74.68 μg/mL, and the instar stage of the mosquito larvae was irrelevant (Morales et al, 2004).…”
Section: Aedes Aegypti Larvae Lethality Bioassays and Chromatographicmentioning
confidence: 92%
“…In the present study, both the employed solvents showed distinct polarities for the extraction of A. vepretorum compounds.Therefore, it was assumed that the acetogenins varied from being very polar -when extracted by water, ethyl alcohol, and methanol -, to being nonpolar when extracted by hexane (Bobadilla et al, 2005). However, there are evidences that extracts obtained with solvents having low and medium polarity are more efficient.…”
Section: Resultsmentioning
confidence: 99%
“…Kotkar et al (2002) considered the phenolic compounds to be phytochemicals with insecticidal activity, based on the action of their hydroxyl groups against the larval enzyme systems (VALENCIA, 1995), which are enzyme systems similar to those involved in the respiratory chain, causing potent inhibition (BOBADILLA, 2005).…”
Section: Resultsmentioning
confidence: 99%